Aortic valve calcium score: does it correlate with mean transaortic gradient?. (3rd October 2022) - Amador, A; Martins Da Costa, C; Calvao, J; Carvalho, J M; Proenca, T; Pinto, R; Marques, C; Cabrita, A; Santos, L; Oliveira, C; Pinho, A; Palma, P; et al.
Abstract: Introduction: Aortic valvular calcium score (AVCS) is useful in patients with aortic stenosis for whom echocardiography was not conclusive in grading its severity. Transcatheter aortic valve implantation (TAVI) is an established procedure of treatment in symptomatic severe AS. The burden of aortic valve calcification has been associated with some TAVI related complications (as perivalvular leaks), but at the same time it is well accepted that some degree of calcification is needed to ensure stable anchoring of the prosthesis to the aortic annulus. Purpose: To assess if there is a correlation between aortic valve calcium score and mean transvalvular gradient 6 months after TAVI – is a higher AVCS correlated with lower mean transaortic gradient after TAVI? Methods: We performed a single-center, retrospective cohort study including patients who underwent TAVI with a preoperative standardized contrast enhanced MSCT with AVCS available. Clinical and echocardiographic data were collected previously to TAVI (pre-TAVI) and at 6 months follow up (6M-FUP). Results: A total of 187 patients were included, with 54% female and a mean age of 79.4±9.0 years old. Most patients had tricuspid aortic valve (95.7%); 5 patients had aortic bicuspidy and 3 had aortic valve bioprothesis. Concerning the valve type, 73.3% had new generation prosthesis and the main valve used was the CoreValve Evolut Pro (33.7%). Also, 38, 5% needed balloon pre-dilation before TAVI. The mean pre-TAVI aortic transvalvular maximum and mean gradients were 76.5±23.2 mmHg and 48.3±15.5 mmHg, respectively; mean aortic valve area was 0.75±0.16 cm 2 . The mean AVCS was 2851±1524 AU (Agaston Units); 81.2% of women had AVCS>1300 AU and 74.4% men had AVCS >2000 AU. Comparing transvalvular aortic gradients previously and 6M-FUP after TAVI, there was an average differential of maximum gradient of 61±22 mmHg and of mean gradient of 40±15 mmHg. A negative and weak correlation was found between the AVCS and the maximum gradient (pearson coefficient of −0.181, p=0.02) and between mean gradient at 6M-FUP (pearson coefficient of −0.191, p=0.014). Discussion and conclusion: AVCS is a significant predictor for death, stroke and perivalvular leaks after TAVI. On the other hand, high AVCS is associated with better seating in the native annulus during deployment. Nevertheless, high AVCS did not strongly correlated with mean transaortic gradient 6 months after TAVI. Funding Acknowledgement: Type of funding sources: None.